Feature: bioinformatics - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Siti Maznah, Kabeb; Noor Suhana, Adzahar (Penerbit UMP, 2010)
Bioinformatics is a field of science in which biology, computer science, and information technology merge to form a single discipline. The term bioinformatics was coined by Paulien Hogeweg in 1979 for the study of informatic processes in biotic systems. Its primary use since at least the late 1980s has been in genomics and genetics, particularly in those areas of genomics involving large-scale DNA sequencing.